Market Reaction Analysis of The Performance from The Winners of Asia Sustainability Reporting Rating Award Companies in 2019 – 2021 - Diajeng Fitri Wulan (Universitas Bangka Belitung, 2022)
Social economic and responsible business is believed to provide opportunities to build competitive advantage, increase market share, and open new markets. This assumption shows that financial and non-financial performance influence the market reaction. The company's non-financial performance can be realized through CSR disclosures disseminated to the public in a sustainability report. On the other hand, the company's financial performance can be seen through the proxies of financial ratios of profitability, liquidity, leverage, and activities as measured using data from the annual report. This study aims to see the effect of the company's performance on the market reaction caused by the information. The sample in this study were all IDX-listed companies that won the Asia Sustainability Reporting Rating Award 2019-2021. So the writer has assumed that the sample in this study has an excellent overall company performance. The data collection methods are historical data sourced from the Indonesian Stock Exchange (IDX). The data used in this research are the company's annual reports and the company's sustainability reports. After passing the classical assumption test stage, the data were analyzed using the multiple regression method. The results show that CSR disclosure, Current Ratio, and Debt to Equity ratio have a positive but insignificant effect. Meanwhile, the Return on Assets and Total Asset Turnover variables significantly positively affect the market reaction. This condition shows that even though the company has won social and environmental awards, financial performance remains a proxy with a more significant influence than non-financial performance.